(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article examines the significant contribution of Uzbek scientists during the second renaissance, the revival of intellectual, cultural and scientific achievements. As a result of the research, the information about science was enslaved by Uzbek scientists in style, studied in depth, and their results were covered. The conclusion provides insight into the long-term impact of their services and offers suggestions for further development of scientific excellence.